(untitled) - Murphy, Kenneth (New York, 2017)
Explore the premier text for immunology at the advanced undergraduate, graduate, and medical school levels. Beginning students appreciate the book’s clear writing and informative illustrations, while advanced students and working immunologists value its comprehensive scope and depth. This edition is thoroughly revised and up to date with significant developments in the field, especially on the topic of innate immunity.
Sinh học miễn dịch
Keywords: Liệu pháp miễn dịch,Immunotherapy